2022
DOI: 10.3390/ijms23126433
|View full text |Cite
|
Sign up to set email alerts
|

Human Amniotic Fluid Stem Cells Ameliorate Thioglycollate-Induced Peritonitis by Increasing Tregs in Mice

Abstract: Mesenchymal stem cells (MSCs) affect immune cells and exert anti-inflammatory effects. Human amniotic fluid stem cells (hAFSCs), a type of MSCs, have a high therapeutic effect in animal models of inflammation-related diseases. hAFSCs can be easily isolated and cultured from amniotic fluid, which is considered a medical waste. Hence, amniotic fluid can be a source of cells for MSC therapy of inflammatory diseases. However, the effect of hAFSCs on acquired immunity in vivo, especially on regulatory T cells, has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In particular, the relationship between hAFSCs and Tregs in vivo has not been investigated, although an in vitro study showed that hAFSCs increased Tregs [28]. Abe et al [29] showed that hAFSCs ameliorated the thioglycollate-induced inflammation, a peritonitis mice model, by forming aggregates with host immune cells, such as macrophages, T cells, and B cells in the peritoneal cavity. Furthermore, the number of regulatory T cells increased in the peritoneal cavity.…”
mentioning
confidence: 99%
“…In particular, the relationship between hAFSCs and Tregs in vivo has not been investigated, although an in vitro study showed that hAFSCs increased Tregs [28]. Abe et al [29] showed that hAFSCs ameliorated the thioglycollate-induced inflammation, a peritonitis mice model, by forming aggregates with host immune cells, such as macrophages, T cells, and B cells in the peritoneal cavity. Furthermore, the number of regulatory T cells increased in the peritoneal cavity.…”
mentioning
confidence: 99%